2018
DOI: 10.1002/jcb.26882
|View full text |Cite
|
Sign up to set email alerts
|

bZIP17 regulates the expression of genes related to seed storage and germination, reducing seed susceptibility to osmotic stress

Abstract: Low temperatures, salinity, and drought cause significant crop losses. These conditions involve osmotic stress, triggering transcriptional remodeling, and consequently, the restitution of cellular homeostasis and growth recovery. Protein transcription factors regulate target genes, thereby mediating plant responses to stress. bZIP17 is a transcription factor involved in cellular responses to salinity and the unfolded protein response. Because salinity can also produce osmotic stress, the role of bZIP17 in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
7
0
2
Order By: Relevance
“…Another regulatory element detected in this genomic region is the putative TF bHLH76 and it has been reported that bHLH is one of the binding factors of the cis-element G-box which was found in promoter regions of all TaMTPs (metal tolerance proteins), which are involved in trace metal homeostasis and have a potential role in cereal grain biofortification with essential micronutrients including Zn ( Menguer et al, 2017 ; Vatansever et al, 2017 ). Additionally, we found that chromosome 5A harbored a TF belonging to the bZIP (basic-region leucine-zipper) family which have a crucial role in nutrient and Zn homeostasis ( Ishimaru et al, 2011 ; Evens et al, 2017 ; Cifuentes-Esquivel et al, 2018 ). In Arabidopsis thaliana , the TFs bZIP19 and bZIP23 were shown to regulate the adaption to Zn deficiency in roots ( Assunção et al, 2010 ; Inaba et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another regulatory element detected in this genomic region is the putative TF bHLH76 and it has been reported that bHLH is one of the binding factors of the cis-element G-box which was found in promoter regions of all TaMTPs (metal tolerance proteins), which are involved in trace metal homeostasis and have a potential role in cereal grain biofortification with essential micronutrients including Zn ( Menguer et al, 2017 ; Vatansever et al, 2017 ). Additionally, we found that chromosome 5A harbored a TF belonging to the bZIP (basic-region leucine-zipper) family which have a crucial role in nutrient and Zn homeostasis ( Ishimaru et al, 2011 ; Evens et al, 2017 ; Cifuentes-Esquivel et al, 2018 ). In Arabidopsis thaliana , the TFs bZIP19 and bZIP23 were shown to regulate the adaption to Zn deficiency in roots ( Assunção et al, 2010 ; Inaba et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under ER stress conditions, transcriptomic changes in vegetative tissues caused by the double mutation of bZIP17 and bZIP60 ( bzip1760 ) are only slightly different from those caused by the single bzip60 mutation, and the single bzip17 mutation also resulted in only subtle changes [ 23 ]. Recent studies revealed that bZIP17 plays important roles in inflorescence tissues [ 30 , 31 , 32 ], with specific target genes including HOMEOBOX 7 (HB-7 ) and DELTA1-PYRROLINE-5-CARBOXYLATE SYNTHASE 1 (P5CS1 ) [ 32 , 33 ].…”
Section: Two Distinct Plant Upr Pathwaysmentioning
confidence: 99%
“…Osmotic stress is another UPR trigger in plants. High-salinity and high-osmolarity conditions trigger the activation of bZIP17 and its translocation to the nucleus [ 31 , 39 ], and the ectopic expression of bZIP17 improved plant resilience to salt stress [ 29 ]. Salt-stress-induced bZIP17 proteolysis was diminished in the single s1p mutant [ 39 ], and the single s2p mutant also exhibited reduced tolerance to desiccation [ 40 ] and reduced sensitivity to abscisic acid (ABA), the plant hormone that mediates drought stress signaling [ 33 ].…”
Section: Upr Action In Stress Responsesmentioning
confidence: 99%
“…Por otro lado, hasta hace poco tiempo sólo se vinculaba a los factores bZIP17 y bZIP28 con una respuesta a proteínas mal plegadas asociadas a situaciones de estrés, tales como salinidad y no a etapas del desarrollo de Arabidopsis thaliana [179]. Sin embargo, actualmente existen trabajos que aseguran que en líneas mutantes del factor bZIP17 sometidas a estrés osmótico, existe una disminución en la expresión de genes asociados al almacenamiento en semillas y la germinación, sugiriendo que este factor puede estar implicado también en la regulación de estos procesos [180] (Cifuentes-esquivel et al, 2018).…”
Section: Discussionunclassified
“…La sobreexpresión de los factores de transcripción del tipo bZIP mencionados en sus formas completa o truncada, ha sido una estrategia estudiada en plantas con el objetivo de sobrellevar distintos cuadros de estrés, confiriendo a las plantas respuestas adaptativas que mejoran su crecimiento en situaciones de sequía o estrés salino entre otros [115]- [118]. Sin embargo, no se ha utilizado a estos factores bZIP en estrategias de ingeniería con el objetivo de aumentar la sobreexpresión de proteínas como sí se ha hecho con sus ortólogos en levaduras y animales [105], [119], [120].…”
Section: 2-estrategias Relacionadas Con La Señal Uprunclassified